The Economics of Laurel Harvesting: Socio-Economic Drivers of Non-Timber Forest Product Utilization in Rural Southern Türkiye - Hasan Emre Ünal (BioResources, 2025)
This study aimed to assess the economic efficiency of laurel harvesting (Laurus nobilis L.) in Andırın, Kahramanmaraş, Türkiye. To achieve this, a household survey with 51 participants involved in laurel harvesting was conducted to identify the socio-economic factors influencing laurel harvesting. Principal component analysis (PCA), Sperman’s correlation analysis, and multiple linear regression modeling were conducted to analyze the relationships between socio-economic factors and laurel harvesting. Exploratory analysis of the dataset showed that laurel is an essential income source for almost 90% of households, particularly during agricultural off-seasons. However, only about 10% of the respondents considered laurel harvesting a profitable business. Statistical analyses revealed that distance to the town-city center, daily harvest earnings, and selling location are key factors in determining profitability from laurel harvesting. The current study’s evidence strongly supported the conclusion that market asymmetries and socio-economic heterogeneity shaped the viability of non-timber forest product-based livelihoods. On the other hand, the findings directly supported the Multiple United Nations Sustainable Development Goals (SDGs), particularly SDG 1 (No Poverty), SDG 8 (Decent Work and Economic Growth), SDG 12 (Responsible Consumption and Production), and SDG 15 (Life on Land). Enhancing local producer autonomy in pricing and market access emerged as a crucial factor in promoting equitable and sustainable laurel utilization in rural forest economies.